Stimulation of Herpesvirus saimiri Expression in the Absence of Evidence for Type C Virus Activation in a Marmoset Lymphoid Cell Line - Neubauer, Russell H. (1974)
Nucleic acid base analogues were used to examine a Herpesvirus saimiri (HVS)-infected marmoset lymphoid cell line (MLC-1) for possible association with type C viruses. Synthetic templates poly(rA)·d(pT)(10) and poly(dA)·d(pT)(10) were used to detect RNA-directed DNA polymerase activity in 100-fold concentrated tissue culture fluids. HVS was monitored by immunofluorescence for early, late, and membrane antigens. MLC-1 cells were exposed to 30 μg of 5-bromo-2′-deoxyuridine (BUdR) per ml for 24 h and examined daily. Similar experiments used 5-iodo-2′-deoxyuridine (IUdR) (20 μg/ml) for 30 h or IUdR (20 μg/ml) for 3 days followed by 2% dimethyl sulfoxide for 4 days. Results of these experiments failed to show any type C virus-like polymerase; however, HVS expression was greatly stimulated. BUdR and IUdR enhanced expression of HVS-associated antigens five- to sevenfold, with maximal stimulation being observed 3 to 4 days after removal of the analogue. IUdR-dimethyl sulfoxide treatment was generally less effective. Although more cells showed HVS antigens, the treatments did not increase cell-free infectious virus. The data suggest that HVS-infected lymphoid cells can be stimulated to express virus in a manner similar to that of the Epstein-Barr virus in Burkitt's lymphoma cells. No evidence of type C virus was found in stimulated cultures.